Development of a core outcome set for trials on induction of labour: an international multistakeholder Delphi study. (10th September 2018) - Dos Santos, F; Drymiotou, S; Antequera Martin, A; Mol, BW; Gale, C; Devane, D; van't Hooft, J; Johnson, MJ; Hogg, M; Thangaratinam, S
Abstract : Objective: To develop a set of core outcomes to be minimally reported in trials on induction of labour. Design: Two‐round Delphi survey and consensus meeting. Population: Four stakeholder groups: midwives, obstetricians, neonatologists, and women's representatives. Methods: Protocol registered with COMET (Registration Number: 695). Stakeholders rated reported outcomes for importance (1—limited to 9—critical). The median rating of each outcome was calculated. The consensus criteria to include outcomes were as follows: ≥70% participants rated outcomes as critical and <15% rated outcomes as limited importance. Outcomes that did not achieve consensus were taken to round two and, if there was still no consensus, to the final consensus meeting. Main outcome measures: Outcomes in trials of induction of labour. Results: Of the 159 invited participants, 54% (86/159) completed the first round, and 83% completed the second round (71/86). The core outcome set included 28 core outcomes in four domains: Short‐term maternal outcomes ( n = 18)—cardiorespiratory arrest, damage to internal organs, death, haemorrhage, hysterectomy, infection, intensive care admission, length of hospital stay, mode of delivery, need for more than one induction agent, oxytocin augmentation, postnatal depression, pulmonary embolus, satisfaction with care, stroke, time from induction to delivery, uterine hyperstimulation, uterine scar dehiscence/rupture; short‐term offspring outcomes ( n = 8)—admission to the neonatal unit, birth trauma, death, hypoxic ischaemic encephalopathy/need for therapeutic hypothermia, meconium aspiration syndrome, need for respiratory support, infection, and seizures; long‐term maternal outcomes ( n = 1)—operative pelvic floor repair; long‐term offspring outcomes ( n = 1)—disability including neurodevelopmental delay. Conclusion: Trials on induction of labour should include this core outcome set to standardise reporting. Tweetable abstract: International multistakeholder Delphi study identifies a core outcome set for trials on induction of labour. Tweetable abstract: International multistakeholder Delphi study identifies a core outcome set for trials on induction of labour.